Preliminary critical nitrogen nutritional indices for lemon balm (Melissa officinalis) grown in a Mediterranean environment in North-Eastern Portugal - Freitas, Sara L. (2014)
The management of crop fertilization presupposes previous diagnoses of soil fertility and plant nutritional status. In Europe, regular soil testing and plant analysis is mandatory for farmers receiving EU subsidies. Soil testing provides information on the potential availability of nutrients in the soil, a key component in the fertilization recommendation systems. By analyzing plant tissues we can access the nutritional status of a crop, which allows understanding if supplemental fertilization is needed. Without these means of diagnostic, fertilization is an entirely empirical practice. The sector of Medicinal and Aromatic Plants (MAP) seems to be out of that logical. For most MAP it were not yet established sufficiency ranges or critical levels that allows the interpretation of plant analysis results (see Mills and Jones, 1996; INIAP-LQARS, 2006). Taken into account that most of MAP production in Europe is organic, and that this may requires the use of expensive commercial organic manures, the situation seems to be unsustainable. There is a real need for sufficiency ranges or critical levels allowing the use of plant analysis as a diagnostic criterion on its nutritional status for a judicious decision on the rate of nutrients to apply. This work is part of a wider project that is still beginning, which main goal is to establish sufficiency ranges or critical levels for some MAP that are having great economic importance in Portugal. In this paper, preliminary results for lemon balm (Melissa officinalis L.) are presented.